ARTISTIC REMINISCENCES IN ARTUR DRON`S BOOK “HEMINGWAY KNOWS NOTHING” - Vivcharyk, Nataliia; Borovska, Khrystyna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article explores artistic reminiscences in the book “Hemingway Knows Nothing” by contemporary Ukrainian writer Artur Dron. It demonstrates that the title of the collection, as well as the titles of the short stories and essays within it, are symbolic and contain both direct and indirect parallels — in particular, with works of world literature, as well as biblical allusions. As a result, a context is created that helps emphasize the causes and brutality of the modern war. The realistic portrayal of events, the prototypes of the characters, and the dialogic nature of the narration point to the author’s need to artistically comprehend and reveal his own experience gained during the war, to record facts and testimonies from both military personnel and civilians. The use of code names, meaningful titles, and symbolic details contains hidden meanings and contributes to the expansion of the thematic scope. The ideological and artistic analysis of the short prose from A. Dron’s collection “Hemingway Knows Nothing” illustrates that the writer seeks to depict the tragedy of war through the portrayal of both individual human lives and the global transformations caused by these tragic events. Through the expressive title of the collection and its constituent works, the author encourages readers to reflect on the socio-political preconditions of military conflicts, addressing issues of heroism and loss, and the preservation of national memory about those Ukrainians who changed the course of history by resisting totalitarianism and defending democratic principles.